Navigating Professional Dilemmas: How Public-Sector Engineers Navigate Ethical Tensions Arising from Conflicting Institutional Logics - Bourdages-Sylvain, Marie-Pierre; Adams, Tracey (Relations industrielles / Industrial Relations, 2024)
Over the last few decades, collegial forms of organization guided by norms of professionalism and shared decision-making have given way in public organizations to more corporate organizational forms that prioritize efficiency and economy. A growing body of research has explored these conflicting institutional logics, and identified the challenges of professional workers as they attempt to reconcile them on the job. At times, however, conflicting logics may create ethical dilemmas for professionals faced with competing imperatives, such as efficiency and public safety, if choosing the ethical imperative threatens their job security or professional standing. Their responses to such dilemmas have been under-explored in the literature. In this paper, we examine such dilemmas, and the responses to them, using qualitative data from public-sector engineers in two Canadian provinces. Public-sector engineers are ideal for such analysis because they work in changing environments where the tension between professional and managerial logics may be keenly felt. We find that these professionals have a range of responses, sometimes resisting and sometimes marginally acceding to workplace pressures. Light is thus shed on the circumstances under which ethical tensions might escalate.